DIFUSI INOVASI DALAM PROGRAM PEMBELAJARAN JARAK JAUH DI YAYASAN TRAMPIL INDONESIA - Teguh, Monika (Scriptura, 2015)
This research aimed to describe the difussion of innovations conducted by TRAMPIL Indonesia Foundation in their â€œLearn and Teachâ€ Program. The program was held to facilitate primary and early childhood education teachers in various places in Indonesia who have difficulty accessing higher education.This program used a combination method in the form of face to face meeting, web conferencing, and learning management system in order to maximize learning outcomes, even though the participants of the program were at remote locations and had different cultural backgrounds. This research was a descriptive qualitative research, using observation and interview as the method of collecting data. The diffusion of innovations here was seen from the innovation of using information and communication technology for long distance learning, the communication channel through interpersonal and group communication, the time of difusion as long as three years, an the penetration through social system such as school and religion institusi. The superiority of this diffusion of innovations was its success for the penetration of new technologies in the underdeveloped regions. The technology brought by TRAMPIL was a cutting-edge technology and even had not been widely used in urban areas. But with a good approach via proper communication channel and social system, this innovation could be received in a relatively short time.